Relevance of Entrepreneurial Orientation and its Effect on the Performance of Smes in Asaba, Delta State - EKURE, Marcus; ELEJE, EDWARD OGBONNIA (Archives of Business Research, 2021)
The study investigated the relevance of entrepreneurial orientation on the performance of Small and Medium scale Enterprises (SMEs) in Delta State. Other specific objectives are to determine the relationship between proactiveness and SMEs performance; to assess the connection between competitive aggressiveness and SMEs performance; to ascertain the connection between risk-taking and SMEs performance. A cross sectional research design was adopted for the study. A structured questionnaire was developed to elicit data from respondents for the study. This study specifically focused on relationship between proactiveness, competitive aggressiveness, innovativeness and the relationship between risk-taking and SMEs performance. All the staff of selected SMEs were sampled. The analytical technique used for hypotheses testing was the chi-square, using Stata version 13. Findings revealed that, all variables used in this study had a significant and positive relationship with performance of SMEs. Thus, the study concludes that entrepreneurial orientation has a significant relationship with performance of Small and Medium scale Enterprises (SMEs). This study therefore recommends amongst others that more intensive entrepreneurial training and practice be done by students in tertiary institutions as there seems to be no job waiting for graduates among the teeming youths we have in Nigeria today.